2020
DOI: 10.1093/cdn/nzaa042_004
|View full text |Cite
|
Sign up to set email alerts
|

Food-Based Dietary Guidelines Make Seafood a Priority, Sustainability an Afterthought

Abstract: Objectives National food-based dietary guidelines (FBDGs) are adapted by governments reflecting their nation's food system and specific nutrition context, with varied approaches by country. Seafood is commonly included as one of many items in a “meat” or “animal-source” food group. It is currently unclear whether FBDG recommendations for seafood are achievable for the food supply, equitable for people, or sustainable for the planet. We seek to (1) Review the specific recommendations of nation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…A number of prior studies have examined the details within different FBDGs, and found that seafood (or fish) was mentioned in 58% [24], 80% [25], 83.5% [27], or 83.7% [26]. A smaller number of FBDGs provided information on either the serving size or the number of meals per week.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A number of prior studies have examined the details within different FBDGs, and found that seafood (or fish) was mentioned in 58% [24], 80% [25], 83.5% [27], or 83.7% [26]. A smaller number of FBDGs provided information on either the serving size or the number of meals per week.…”
Section: Resultsmentioning
confidence: 99%
“…A smaller number of FBDGs provided information on either the serving size or the number of meals per week. Graham et al [26] found that 35 FBDGs reported servings per week, and Herforth et al [24] reported an average of 2.2 servings per week, but only 23 provided the serving size. It is difficult to generalize serving size given the wide variability in how this metric is reported.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations